2004
DOI: 10.1103/physrevb.70.024303
|View full text |Cite
|
Sign up to set email alerts
|

Elastic wave propagation through a random array of dislocations

Abstract: International audienceA number of unsolved issues in materials physics suggest there is a need for an improved quantitative understanding of the interaction between acoustic (more generally, elastic) waves and dislocations. In this paper we study the coherent propagation of elastic waves through a two dimensional solid filled with randomly placed dislocations, both edge and screw, in a multiple scattering formalism. Wavelengths are supposed to be large compared to a Burgers vector and dislocation density is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 49 publications
3
63
0
Order By: Relevance
“…(21). Note also that the two dimensional problem of transverse (anti-plane) waves scattered by an infinite straight screw dislocation is a scalar Schrödinger problem 19 with a potential k|V |k proportional to k 2 . The analysis we review below also holds when the point obstacle is modelled by even derivatives of the delta function 20 .…”
Section: Comparison With the Renormalization Of A Dirac Delta Potentimentioning
confidence: 99%
“…(21). Note also that the two dimensional problem of transverse (anti-plane) waves scattered by an infinite straight screw dislocation is a scalar Schrödinger problem 19 with a potential k|V |k proportional to k 2 . The analysis we review below also holds when the point obstacle is modelled by even derivatives of the delta function 20 .…”
Section: Comparison With the Renormalization Of A Dirac Delta Potentimentioning
confidence: 99%
“…Previous results have shown that distributed crack-like defects may cause a decrease in the phase velocity and an increase in the wave attenuation. The efficiency and the applicability ranges of 2D homogenization analysis of elastic wave propagation through a random array of scatters of different shapes and dilute concentrations based on the BEM and Foldy-type dispersion relations were demonstrated also by many authors, for instance, by Maurel et al [20], Sato and Shindo [21], Tourin et al [22]. However, to the author's knowledge, the overall average dynamic response of 3D composite material containing randomly distributed and movable penny-shaped inclusions with a much larger rigidity than that of the matrix material has not been investigated for moderate and high frequencies.…”
Section: Introductionmentioning
confidence: 82%
“…With Eq. (20), the amplitude of a plane time-harmonic elastic wave propagating in the n -direction can be expressed as…”
Section: Scattering By Distributed Inclusions: Determination Of the Ementioning
confidence: 99%
“…Previous results have shown that distributed crack-like defects may cause a decrease in the phase velocity and an increase in the wave attenuation. The efficiency and the applicability ranges of 2D homogenization analysis of elastic wave propagation through a random array of scatters of different shapes and dilute concentrations based on the BEM and Foldy-type dispersion relations were demonstrated also by many authors, for instance, in the papers [13,14]. In 3D case this approach was applied for the numerical simulation of the average dynamic response of composite material containing rigid disk-shaped inclusions of equal mass only [15].…”
Section: Introductionmentioning
confidence: 99%